Beyond the cemetery of the living: an exploration of disposal and the politics of visibility in the Nicaraguan prison system - Weegels, Julienne (Carceral communities in Latin America, 2021)
While prison authorities enforce the penitentiary both as a dumpster for “animals” and a reformatory for “doubly failed” men, prisoners’ lives and livelihood become doubly precarious. Disposed of through a politics of mediated naming and shaming, their commonplace refrain of being stuck in the “cemetery of the living” grounds this chapter’s focus on the practices prisoners engage in to reckon with and to undo their social disposal, largely arranged around the ideal of penal reeducation and “change of attitude”. Yet how do these changes articulate with(in) the violent realities of the “cemetery,” and the challenges prisoners face during their “social reinsertion”? Drawing from extensive field research in the Nicaraguan prison system, this chapter seeks to problematize the institutionalization of disposal by analyzing (former) prisoners’ parallel engagement in performances of violence and change.